2014
DOI: 10.1177/0898264314527479
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Coagulation as Mediators in the Relationships Between Religious Attendance and Functional Limitations in Older Adults

Abstract: Objective To examine inflammation and coagulation, which are positively linked to disability and inversely linked to increased religious attendance, as mediators in the cross-sectional relationships between religious attendance and functional status. Methods Frequency of attendance and limitations in basic activities of daily living (ADLs), instrumental activities (IADLs) and mobility were assessed in 1,423 elders. Results More frequent attendance was associated with fewer ADL, IADL, and mobility limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Our review of the literature revealed that only seven studies have formally tested any of these processes (Benjamins 2004;Hybels et al 2014;Idler 1987;Kasl 1992, 1997b;Krause and Hayward 2012;Son and Wilson 2011). Interestingly enough, there is no empirical evidence of mediation for body mass, alcohol consumption, marital status, contact with friends and children, social well-being, the provision of emotional support, optimism, fatalism, emotional well-being, depression, and psychological well-being (Idler 1987;Kasl 1992, 1997b;Son and Wilson 2011).…”
Section: Model 1: Health Causationmentioning
confidence: 99%
See 4 more Smart Citations
“…Our review of the literature revealed that only seven studies have formally tested any of these processes (Benjamins 2004;Hybels et al 2014;Idler 1987;Kasl 1992, 1997b;Krause and Hayward 2012;Son and Wilson 2011). Interestingly enough, there is no empirical evidence of mediation for body mass, alcohol consumption, marital status, contact with friends and children, social well-being, the provision of emotional support, optimism, fatalism, emotional well-being, depression, and psychological well-being (Idler 1987;Kasl 1992, 1997b;Son and Wilson 2011).…”
Section: Model 1: Health Causationmentioning
confidence: 99%
“…Interestingly enough, there is no empirical evidence of mediation for body mass, alcohol consumption, marital status, contact with friends and children, social well-being, the provision of emotional support, optimism, fatalism, emotional well-being, depression, and psychological well-being (Idler 1987;Kasl 1992, 1997b;Son and Wilson 2011). There are, however, some data to support the partial mediating influence of physical activity, smoking, contact with family, leisure social activities, meaning in life, and immune function (Benjamins 2004;Hybels et al 2014;Idler and Kasl 1997b;Krause and Hayward 2012). Taken together, these results suggest that religious involvement may actually contribute to better physical functioning through a range of mechanisms.…”
Section: Model 1: Health Causationmentioning
confidence: 99%
See 3 more Smart Citations